Transmitted drug resistance and phylogenetic analysis of HIV-1 virus from Kelantan, Malaysia based on Reverse Transcriptase (RT) gene - Ching, Hii Siew (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Although the introduction of antiretroviral (ARV) treatment has been associated with marked decreases in HIV-related morbidity and mortality, its effectiveness is limited by the emergence of drug resistance. This study was conducted to determine the presence of transmitted HIV drug resistance (THIVDR) viruses and phylogenetic analysis of HIV-1 virus from naive ARV therapy patients from Kelantan, Malaysia based on RT gene. Our interest was on THIVDR as it makes ARV treatment more complicated and costly and there is limited information on transmitted HIVDR viruses were amplified and sequenced. After that, specific mutations of RT gene associated with drug resistance were analyzed using Standford HlVdb: Genotypic Resistance Interpretation Algorithm and HIV LANL ADRA: Antiviral Drug Resistance Analysis. From the result, mutations K101Q and K103N were identified in 3 and 1 of the studied HIV viruses respectively. These viruses are expected to have resistance to Nucleoside reverse-transcriptase inhibitors (NNRTI) Efavirenz drugs. Subsequently, these sequences were phylogenetically analyzed to determine the source and subtype of the viruses. Phylogenetic result showed that out of 10 HIV-1 viruses used in this study, 9 were of the CRF01AE subtype and only one was under CRF01AE/B subtype. This study also found that Kelantan HIV-1 viruses had high similarity (97-99%) to the Thailand HIV-1 viruses because these countries share a border with each other. In conclusion, transmitted HIVDRs were successfully identified in Kelantan, Malaysia. However, further study involving larger samples to determine the actual prevalence of THIVDR in Kelantan need to be carried out.